Gambaran Tingkat Kepuasan Tenaga Kerja Terhadap Program K3 Dibagian AMP (Asphalt Mixing Plant) PT. Prima Pembangunan Kerinci Tahun 2017 - Aulia Azhar; Dina Waldani (Badan Penelitian and Pengembangan (Balitbang), Padang, West Sumatra, Indonesia, 2018)
K3 program aimed to provide security for employees in carrying out their work and reduce company costs. If work accidents and illness arise due to work relations, occupational safety and health (K3) must be a top priority in all companies in order to achieve satisfaction. The purpose of this study was to find out the description of the level of workforce satisfaction with the K3 program in the AMP (Asphal Mixing Plant) section of PT. Kerinci Development in 2017. The design of this study was descriptive. The population is all labor in PT. Prima Pembangunan Kerinci AMP section with 30 samples. The method of sampling with total sampling technique, the study was conducted in March - August 2017 and the research instrument using a questionnaire. Based on the results of the study as many as 13 workers (43.3%) were not satisfied with work safety and as many as 17 workers (56.7%) were not satisfied with the work health of the K3 program in the AMP (Asphal Mixing Plant) PT. Prima Pembangunan Kerinci in 2017. It is hoped that the company leaders will conduct routine health checks every month and also leaders pay more attention to employee safety by providing training on awareness of using personal protective equipment and introducing personal protective equipment and ways of using it, so that employees can use at any time in the event of a work accident.